(untitled) (International Journal of Studies in Nursing, 2020)
Ultrasound is a safe diagnostic tool used in pregnancy to detect significant causes of foeto-maternal mortality. We explored the reasons for an obstetric scan in 400 randomly selected pregnant women attending a low-cost ultrasound centre in Nigeria. We used a cross-sectional analysis using a structured interviewer-administered questionnaire. The results showed that the participants were aged 27.37±5.96 years, 76% literate, 68.5% Muslims, 50.5% small-scale self-employees, and 31.45% grand-multiparous. The reasons for an obstetric scan were foetal well-being (44.2%), referral by a health worker (34%), gender determination (9.7%), vaginal bleeding (4.8%), confirmation of pregnancy (2.6%), due-date determination (2.5%), foetal weight estimation (2.1%), and foetal number (0.1%). Spouse education with foetal wellbeing (p = .001), gender determination (p = .002), and dating of gestation (p = .002); participants’ occupation with referral by a health worker (p = .026) and confirmation of pregnancy (p = .044); spouse occupation with foetal wellbeing (p = .004) and vaginal bleeding (p < .001); daily household income with referral by a health worker (p < .001) and pregnancy dating (p = .005); and religion with gender determination (p = .007). Health education and improved access to ultrasound services will go a long way in improving maternal/child health.